Analysis of quantitative magnetic resonance imaging and biomechanical parameters on human discs with different grades of degeneration. Issue 6 (30th April 2013) - Antoniou, John; Epure, Laura M.; Michalek, Arthur J.; Grant, Michael P.; Iatridis, James C.; Mwale, Fackson
<x xml:space="preserve">Abstract</x> Purpose To establish relationships between quantitative MRI (qMRI) and biomechanical parameters in order to help inform and interpret alterations of human intervertebral discs (IVD) with different grades of degeneration. Materials and Methods The properties of the nucleus pulposus (NP) and annulus fibrosus (AF) of each IVD of 10 lumbar spines (range, 32–77 years) were analyzed by qMRI (relaxation times T1 and T2, magnetization transfer ratio [MTR], and apparent diffusion coefficient [ADC]), and tested in confined compression and dynamic shear. Results T1 and T2 significantly decreased in both the NP and AF with increasing degeneration grades while the MTR increased significantly with grade 4. In contrast to the other qMRI parameters, the ADC had a tendency to decrease with increasing grade. Disc degeneration caused a decrease in the aggregate modulus, hydraulic permeability and shear modulus magnitude along with an increase in phase angle in the AF. In contrast, disc degeneration of NPs demonstrated decreases in shear modulus and phase angle. Conclusion Our studies indicate that qMRI can be used as a noninvasive diagnostic tool in the detection of IVD properties with the potential to help interpret and detect early, middle, and late stages of degeneration. QMRI of human IVD can therefore become a very important diagnostic assessment tool in determining the functional state of the disc. J. Magn. Reson. Imaging 2013;38:1402–1414. © 2013 Wiley Periodicals, Inc.